Identification of Cardiovascular Risk Factors in Obese Adolescents With Metabolic Syndrome - Lee, Jung Won; Hong, Young Mi; Kim, Hae Soon (Frontiers in Pediatrics, 2021)
Objective: There are studies that show different associations between metabolic syndrome (MS) and cardiovascular disease in adolescent. This study is aimed to identify probable cardio-vascular risk factors in obese adolescents with MS. Methods: Sixty-five obese adolescents with a body mass index (BMI) > 95 percentile were enrolled and divided into two groups with MS or without MS. Left ventricular mass (LVM), left ventricular mass index, ejection fraction, epicardial fat thickness, visceral fat thickness (VFT) and carotid intima-media thickness were measured. Anthropometric and blood chemistry parameters were estimated. Above parameters were compared based on presence or absence of MS. Results: The prevalence of MS was 23.1% in obese adolescents. LVM showed significant correlation with body mass index (BMI), hip circumference (HC), fat mass, total cholesterol (TC), LDL-cholesterol (LDL-C) and waist circumference (WC). VFT significantly correlated with WC, BMI, hip circumflex (HC), obesity index (OI), fat %, fat mass, insulin, TC, LDL-C, insulin, triglyceride (TG), glucose, homeostatic model assessment for insulin resistance (HOMA-IR) and leptin. Conclusions: Screening for the MS in overweight adolescents may help to predict risk of future cardiovascular disease. These data suggest that LVMI and VFT are significant parameters for predicting cardiovascular disease risk in obese adolescents.